Chemical Upcycling of Waste Poly(bisphenol A carbonate) to 1, 4, 2‐Dioxazol‐5‐ones and One‐Pot C−H Amidation. Issue 19 (2nd July 2021) - Jung, Hyun Jin; Park, Sora; Lee, Hyun Sub; Shin, Hyun Gyu; Yoo, Yeji; Baral, Ek Raj; Lee, Jun Hee; Kwak, Jaesung; Kim, Jeung Gon
Abstract: Chemical upcycling of poly(bisphenol A carbonate) (PC) was achieved in this study with hydroxamic acid nucleophiles, giving rise to synthetically valuable 1, 4, 2‐dioxazol‐5‐ones and bisphenol A. Using 1, 5, 7‐triazabicyclo[4.4.0]‐dec‐5‐ene (TBD), non‐green carbodiimidazole or phosgene carbonylation agents used in conventional dioxazolone synthesis were successfully replaced with PC, and environmentally harmful bisphenol A was simultaneously recovered. Assorted hydroxamic acids exhibited good‐to‐excellent efficiencies and green chemical features, promising broad synthetic application scope. In addition, a green aryl amide synthesis process was developed, involving one‐pot depolymerization from polycarbonate to dioxazolone followed by rhodium‐catalyzed C−H amidation, including gram‐scale examples with used compact discs. Abstract : Make it green : Chemical upcycling of poly(bisphenol A carbonate) (PC) to synthetically valuable 1, 4, 2‐dioxazol‐5‐one is realized. In addition to toxic bisphenol A recovery, waste PC replaces phosgene or its derivatives in a carbonylation reaction, boosting the metrics of green chemistry.